THE ROLE OF PUBLIC POLICY IN STRENGTHENING THE ENFORCEMENT OF ADMINISTRATIVE LAW IN INDONESIA - Syam, Fauzi; Yusra Pebrianto, Dony; Bambang Marsudi, Eko; Amala Rizki, Khana (Progressive Law Review, 2025)
Administrative law is a fundamental instrument in realizing a transparent, accountable, and equitable government. However, its implementation in Indonesia still faces various challenges, including jurisdictional conflicts between judicial bodies, the lack of public legal awareness, limited human resources, and suboptimal technological infrastructure. This study aims to analyze the role of public policy in strengthening the enforcement of administrative law through regulatory reform, the digitalization of the judicial system, and the enhancement of public participation. The research method used is a normative legal approach, analyzing legislation, legal doctrines, and national and international scholarly literature. The findings show that public policy plays a central role in supporting the transformation of the administrative legal system. The implementation of Law No. 30 of 2014 on Government Administration has expanded the authority of the Administrative Court (PTUN) to adjudicate on government actions that were previously outside the reach of the law. Additionally, judicial digitalization through the e-Court system has proven to expedite case handling processes and enhance public access to justice, particularly in remote areas. Strengthened public participation through Law No. 25 of 2009 and Law No. 14 of 2008 also contributes to reinforcing oversight over state administrative practices. However, the effectiveness of these policies is still limited by implementation challenges, which require further policy strategies such as regulatory harmonization, public legal education, and investment in infrastructure and human resources